Pemetaan Preferensi Perilaku Pemilih Milenial Pada Pilkada Kabupaten Tanah Datar 2020 - Budiman, Novi; Irwandi, Irwandi (POLITEA, 2020)
Mapping Millennial Voter Behavior PreferencesIn the 2020 Tanah Datar District- Millennial generation in the election and election contest in Indonesia has recently become the center of attention of many groups. This is reasonable because it is estimated that 35% -40% of voters in Indonesia are from this generation. This generation, known to be close to the cyber world, is considered by many to be a critical, creative and rational generation. This study aims to map the preferences of millennial voters in the Tanah Datar District Election in 2020. The study used a survey method with 200 respondents